Virtual Multimedia E-tour system / Yong Teik Hwa - Yong , Teik Hwa (2002)
Virtual Multimedia E-tour system is a tourism system which has a concept of multimedia in presenting the information in the sense of virtual in the website. The system is in English version. The selected destination is Penang. This system is consist of five main module which are General Info, Kek Lok Si, Batu Feringghi, Video and Email. Virtual Multimedia E-tour system is built for exploiting multimedia particles. This system generates a virtual scene so that that the tourists will feel the real destination before they go to the destination. Besides, this system is also built globally to promote the tourism information. In spite, building this system will reduce the expenses of sending information and to avoid operating information manually.In building Virtual Multimedia E-tour system, Waterfall Module and Prototype module is used as module reference. This is because of these modules have the characteristic of verification and validation that ensure the process system is built systematically. The Software used in building the Virtual Multimedia E-tour System is Flash 5, DV Studio, Microsoft Paint, ArcSoft PhotoImpressiom 2000, MP3 To Wave Converter and Nero-Burning Rom.